2011
DOI: 10.1021/ie102479m
|View full text |Cite
|
Sign up to set email alerts
|

Stearic Acid-Coated Chitosan-Based Interpenetrating Polymer Network Microspheres: Controlled Release Characteristics

Abstract: Novel pH-sensitive stearic acid-coated interpenetrating polymer network (IPN) blend microspheres of chitosan and gelatin were prepared by the emulsion cross-linking method using glutaraldehyde for the controlled release (CR) of isoniazid (INH), an antituberculosis drug. Coated as well as uncoated microspheres were developed and characterized by Fourier transform infrared (FTIR) to understand the chemical interactions and formation of the IPN blend structure as well as to confirm successful coating with the ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 32 publications
(50 reference statements)
0
28
0
1
Order By: Relevance
“…Utilization of coating materials such as stearic acid on the surfaces of chitosan-based PECs could further reduce the burst release in the gastric media. However, stearic acid does not seem to be stable as a coating matrix in alkaline media because of the ionization; thereby, the release of loaded isoniazid-coated formulations in alkaline media is higher than the uncoated formulation [36]. An example of the pH-dependent controlled drug release manner of the stearic-acid-coated formulation is depicted in Fig.…”
Section: Chitosanmentioning
confidence: 99%
“…Utilization of coating materials such as stearic acid on the surfaces of chitosan-based PECs could further reduce the burst release in the gastric media. However, stearic acid does not seem to be stable as a coating matrix in alkaline media because of the ionization; thereby, the release of loaded isoniazid-coated formulations in alkaline media is higher than the uncoated formulation [36]. An example of the pH-dependent controlled drug release manner of the stearic-acid-coated formulation is depicted in Fig.…”
Section: Chitosanmentioning
confidence: 99%
“…These peaks were assigned to C-H stretching vibration of -CH 2 groups and indicated that adipic acid reacted with CaCO 3 . In the case of CAC(e), compared with the spectrum of chitosan and adipic acid-coated CaCO 3 , the peak shifted from 1652 cm -1 to 1638 cm--1 and an extra carboxylate anion band appeared at 1560 cm -1 , indicating electrostatic interactions between adipic acid and chitosan (27). It is reasonable to conclude that chitosan was crosslinked with adipic acid by ionic interactions (29,30) and successfully coated on adipic acid modified CaCO 3 .…”
Section: Ft-ir Analysismentioning
confidence: 93%
“…Figure 1 shows FT-IR spectra of chitosan (a), adipic acid (b), naked CaCO 3 (c), adipic acid-coated CaCO 3 (d), and CAC (e). In the case of chitosan (a), a broad band observed at 3452 cm -1 can be assigned to the stretching vibrations of O-H and N-H (26), while the band at 1652 cm -1 represents the presence of the carbonyl of the amide group stretching vibrations (27). In the spectrum of CaCO 3 (c), the peaks appearing at 1431 and 874 cm -1 were attributed to asymmetric C-O stretching and out-of-plane deformation of CO 3 (28).…”
Section: Ft-ir Analysismentioning
confidence: 99%
“…. The deviation of n value below indicated that it can also be due to the complexity of the biocomposites system with a high heterogeneity (Angadi et al 2011).…”
Section: )mentioning
confidence: 97%